The Impact of Oil Price Fluctuations on Inflation in Algeria during the period (1990-2021) - amroun, wissame; smaali, faouzi (Finance and Business Economies Review, 2022)
This research paper aims to know the impact of oil price fluctuations on inflation in Algeria during the period from 1990 to 2021 using an autoregressive Var model. Where after examining the stability of the time series of the variables under study, it was found that they are stable at the first differences. After doing the Engel and Granger co-integration test, it was found that there is no long-term co-integration relationship between oil prices and the inflation rate, which made us rely on the autoregressive model. The study concluded with a set of results, namely the absence of a causal relationship between the two variables during the study period, in addition to the fact that the impact of oil price fluctuations on inflation amounted to a large percentage estimated at 74%, while the remaining percentage was caused by other factors.